2004
DOI: 10.1007/s00018-003-3460-6
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide fragments stimulate glucose utilization in diabetic rats

Abstract: Studies of C-peptide cellular effects show that not only the full-length native peptide but also specific C-terminal fragments are biologically active in in vitro systems. In the present study, the effect of five C-peptide fragments and the native peptide on whole-body glucose turnover was studied in streptozotocin diabetic rats using the insulin clamp technique. Insulin was infused intravenously at 18 pmol kg(-1) min(-1) for 90 min and blood glucose concentration was clamped at 8 and 4 mM in diabetic and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
(32 reference statements)
3
18
0
Order By: Relevance
“…This lowering effect of C-peptide on blood glucose has previously been described [28]. Sato and co-workers showed that EVARQ increased glucose turnover to the same extent as the intact C-peptide [29], suggesting that the active site within the C-peptide that mediates these metabolic effects is located within the EVARQ sequence.…”
Section: Discussionmentioning
confidence: 67%
“…This lowering effect of C-peptide on blood glucose has previously been described [28]. Sato and co-workers showed that EVARQ increased glucose turnover to the same extent as the intact C-peptide [29], suggesting that the active site within the C-peptide that mediates these metabolic effects is located within the EVARQ sequence.…”
Section: Discussionmentioning
confidence: 67%
“…2). Glu27 is not only involved in C-peptide cellular membrane interactions and Ca 2+ responses [19,21] but is also required for induction of phosphorylation of ERK1/2. Similarly, lack of Glu at positions 3 and 11 results in loss of C-peptide stimulation of ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of C-peptide is unordered under physiological conditions, while the N-terminal part (residues 1-11) can adopt an a-helical conformation in high concentrations of trifluoroethanol (TFE) [19]. Other evidence suggests that the C-terminal pentapeptide part of C-peptide has an activity similar to that of full-length C-peptide in displacing C-peptide bound to a cell surface [16], in molecular assays [17,20] and in stimulating glucose utilisation in diabetic rats [21]. Glu27 seems to be important for binding to cell surfaces [22].…”
mentioning
confidence: 96%
“…Diabetic complications have long been considered irreversible. However, there are emerging possibilities of reversal of diabetic renal injury, since leptin treatment alleviates glomerular injury and proteinuria in an experimental mouse model of diabetic nephropathy [156][157][158][159][160], and pancreas transplantation reduces diabetic lesions after ten years of normoglycemia [161]. The latter brings about a need for further studying the metabolic properties of proinsulin Cpeptide, a molecule believed to influence both eNOS and insulin signaling [23].…”
Section: Future Therapeutic Targets For Prevention Of Diabetic Nephromentioning
confidence: 99%